Pengaruh Pola Asuh Demokratis terhadap Kedisiplinan dan Hasil Belajar PJOK Siswa SMP Negeri Ngusikan - Arie Amalia Firdaus; Rahayu Prasetiyo; Risfandi Setyawan (Universitas Majalengka, 2022)
Differences in indicators of democratic parenting in parenting children can determine discipline and learning outcomes. There are 5 indicators of democratic parenting including guidance, deliberation, communication, appreciation, and direction. But among the five indicators of democratic parenting, it is not yet known which one can affect discipline and learning outcomes.This study aims to determine the effect of democratic parenting on discipline and learning outcomes of Physical Education Sports and Health students at SMP Negeri Ngusikan. Based on the type, this research is a quantitative research with the Ex post facto method to show that the independent variable has occurred before and is not manipulated by the researcher. In this study, there are independent variables, namely democratic parenting and the dependent variable is discipline and learning outcomes. The sample in this study amounted to 182 students. The data collection in this study used a democratic parenting and discipline questionnaire which was filled in through the google form media.Based on the results of calculations using Manova (Multivariate Analysis of Variance) through the SPSS program, there is no significant effect between democratic parenting on discipline and student learning outcomes with significant values ​​of 0.447 and 0.549 or > 0.05. However, the results obtained indicate that communication has a major influence on discipline and learning outcomes, then followed by deliberation, appreciation, direction and finally guidance.